Ultrasonography estimates of fetal growth in fetuses affected by trisomy 21. Issue 3 (24th February 2016) - Bernstein, Sarah N.; Saller, Devereux N.; Catov, Janet M.; Canavan, Timothy P.
Abstract: Objective: To construct growth curves specific for fetuses with trisomy 21 (T21) and to compare them with the reference‐based standard. Methods: A retrospective cohort study was conducted of ultrasonography examinations from women with singleton pregnancies with a confirmed diagnosis of T21 who sought care at an academic tertiary‐care center in the USA between January 1, 2003, and December 31, 2013. Growth curves were constructed using linear regression and compared with the Hadlock standard. Results: The study included 425 ultrasonography examinations from 235 women. The head circumference and femur length were smaller than the reference standards at all gestational ages (head circumference: P = 0.017; femur length: P < 0.001). The abdominal circumference was larger than the reference standard from 29 weeks onward ( P < 0.001). The biparietal diameter was smaller in the second trimester and in the late third trimester ( P < 0.001). The overall estimated fetal weight was not different from the reference standard. Conclusion: The T21‐specific growth curves indicate anthropometric differences between T21 fetuses and the general population. Once validated, such individual growth curves could allow for more accurate prenatal assessment and management of fetuses affected by T21.